Armed Conflict as a Tool of Politics: Terrorism, Guerilla or Partisan Warfare - Jovanović, Dejan; Milašinović, Srđan (NBP. Nauka, bezbednosti, policija, 2025)
The research problem of this paper is related to the determination of similarities and differences between terrorism, guerrilla and partisan warfare, on specific examples that are processed through case studies. The main goal is to determine the correlation between political victory and armed victory in armed political conflicts. The main result is a scientific explanation of the often confusing relation between combat casualties on the one hand and the political outcomes of armed conflict on the other. The conclusion drawn from the research results tells us how decision-makers should assemble teams to combat threats to national security.